2021
DOI: 10.3390/ijms22168460
|View full text |Cite
|
Sign up to set email alerts
|

The Immunometabolic Roles of Various Fatty Acids in Macrophages and Lymphocytes

Abstract: Macrophages and lymphocytes demonstrate metabolic plasticity, which is dependent partly on their state of activation and partly on the availability of various energy yielding and biosynthetic substrates (fatty acids, glucose, and amino acids). These substrates are essential to fuel-based metabolic reprogramming that supports optimal immune function, including the inflammatory response. In this review, we will focus on metabolism in macrophages and lymphocytes and discuss the role of fatty acids in governing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 124 publications
1
11
0
Order By: Relevance
“…Thus, Dangardt et al demonstrated that n -3 MUFA supplementation increases serum levels and decreases TNFα, IL-6, and IL-1β levels in the PBMCs of subjects with obesity [ 114 ]. In line with this, Zhao et al revealed that the treatment of people with obesity with n -3 MUFAs, such as linolenic acid, decreases free plasma FAs, IL-6, and TNFα levels and increase PPARγ expression in mononuclear cells (PBMCs) [ 11 , 115 ]. Furthermore, oleic acid (OA) is an n -9 MUFA, recognized as a versatile nutraceutical and effective biomolecule, with potent antioxidant capacity because it can directly regulate both the synthesis and the activity of antioxidants enzymes [ 158 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, Dangardt et al demonstrated that n -3 MUFA supplementation increases serum levels and decreases TNFα, IL-6, and IL-1β levels in the PBMCs of subjects with obesity [ 114 ]. In line with this, Zhao et al revealed that the treatment of people with obesity with n -3 MUFAs, such as linolenic acid, decreases free plasma FAs, IL-6, and TNFα levels and increase PPARγ expression in mononuclear cells (PBMCs) [ 11 , 115 ]. Furthermore, oleic acid (OA) is an n -9 MUFA, recognized as a versatile nutraceutical and effective biomolecule, with potent antioxidant capacity because it can directly regulate both the synthesis and the activity of antioxidants enzymes [ 158 ].…”
Section: Resultsmentioning
confidence: 96%
“…This implies an active characteristic metabolic state: while M1 macrophages primarily use glucose consumption and lactate excretion, M2 macrophages use OXPHOS, FAO, and mitochondrial respiration [ 69 ]. Thus, Rosa et al proposed that FAO induces M2 [ 11 , 70 ]. Moreover, the repolarization of M2 to M1 after infection conditions with the consequent metabolic reprogramming leads to an impaired TCA cycle in M1 and succinate accumulation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 macrophages are involved in the resolution, activated during the repair phase of functional activity of tissue injury, through OXPHOS and FAO as the main functional pathways ( 28 ). There is also evidence that FAO induces M2 phenotypic transformation, although whether this process is sufficient for M2 polarization has not been fully elucidated ( 29 ), inhibiting fatty acid transporter proteins promotes their M1 phenotype ( 30 ). Therefore, we are not yet able to determine the causal relationship between reprogramming of FAO energy utilization and M2 polarization behavior.…”
Section: Differences In Metabolic Reprogramming Macrophagesmentioning
confidence: 99%
“…Obesity results from an imbalance between energy intake and expenditure, in which the excess energy is stored as triglyceride in white adipose tissue with both increased fat cell size (hypertrophy) and number (hyperplasia) [18]. Obesity induces a state of chronic, low-grade inflammation in fat that is accompanied by the local secretion of cytokines and chemokines, causing attenuation of insulin action [19][20][21][22][23]. Obesity is closely associated with a number of diseases including type 2 diabetes (T2D), cardiovascular disease, hypertension, dementia, and certain cancers [24,25].…”
Section: Introductionmentioning
confidence: 99%